2015
DOI: 10.1016/j.exmath.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Invariant subspaces and Deddens algebras

Abstract: It is shown that if the Deddens algebra DT associated with a quasinilpotent operator T on a complex Banach space is closed and localizing then T has a nontrivial closed hyperinvariant subspace.Ministerio de Economía y CompetitividadJunta de Andalucí

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In this article, we find other less restrictive assumptions under which these inequalities hold. Closely related conditions to our assumptions have already appeared in different contexts (see, e.g., [13], [12], [15], [8], and the references therein). The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this article, we find other less restrictive assumptions under which these inequalities hold. Closely related conditions to our assumptions have already appeared in different contexts (see, e.g., [13], [12], [15], [8], and the references therein). The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 59%
“…Note that the conditions ac = ca, bc = cb, and ab = cba, where c is powerbounded, are natural. Operators satisfying closely related conditions have already been studied in the context of spectral algebras and related invariant subspace problems (see, e.g., [13,Proposition 2.3], [12], [15], [8], and the references therein).…”
Section: Related Results In Banach Algebrasmentioning
confidence: 99%
“…The study of the Deddens algebra was originally introduced by Deddens [14], where he assumed that A is an invertible operator and . Later, it received the attention of many scholars (see [14, 19, 20, 3437, 42, 43]). Recently, Petrovic and Sievewright [37] studied the Deddens algebra associated with compact composition operators on Hardy spaces, where A is not necessarily invertible, and they have demonstrated that the operators and belong to the Deddens algebra .…”
Section: Deddens Algebrasmentioning
confidence: 99%
“…The advantage about our proposed definition is that A can not be an invertible operator. For details and facts about Deddens algebra, we refer the reader to [10,13,15,16,19]. Multiplication operator M h is defined to be M h f (z) = h(z)f (z) for h ∈ H ∞ (D) and f ∈ H p .…”
Section: Introductionmentioning
confidence: 99%